Hybrid VS2 cocatalyst and phosphorus dopant towards both surface and bulk modification of ZnCdS/CdS heterostructures. Issue 3 (15th January 2019) - Zhang, Yu; Lin, Ye-Zhan; Wang, Zhao-Xu; Li, Kui; Li, Tao; Liu, Fu-Tian
Abstract : The bulk phosphorus doping and the surface VS2 modification over ZnCdS–CdS show synergistic effects for improving its photocatalytic activity. Abstract : Rationally designing a photocatalytic system is of significance for effectively converting infinite solar energy into clean hydrogen energy. This study revealed that bulk modification of ZnCdS–CdS heterojunction via phosphorus doping and surface modulation by adopting the novel VS2 as the cocatalyst exhibited synergistic effects for improving the photocatalytic activity of the heterojunction. Notably, the photocatalytic hydrogen evolution rate of the pristine ZnCdS–CdS heterostructure raised from 25.46 to 72.82 and 52.82 μmol h −1 using only 5 mg photocatalyst with the bulk and surface modification alone, respectively, while the hydrogen evolution rate increased to 192.28 μmol h −1 with both bulk phosphorus doping and surface adoption of VS2, opening a new method for the improving the photocatalytic activity by both bulk and surface modulation.